Effectiveness and cost-effectiveness of psychiatric mother and baby units: quasi-experimental study. (October 2022) - Howard, Louise M.; Trevillion, Kylee; Potts, Laura; Heslin, Margaret; Pickles, Andrew; Byford, Sarah; Carson, Lauren E.; Dolman, Clare; Jennings, Stacey; Johnson, Sonia; Jones, Ian; McDonald, Rebecca; et al.
Abstract : Background: Psychiatric mother and baby units (MBUs) are recommended for severe perinatal mental illness, but effectiveness compared with other forms of acute care remains unknown. Aims: We hypothesised that women admitted to MBUs would be less likely to be readmitted to acute care in the 12 months following discharge, compared with women admitted to non-MBU acute care (generic psychiatric wards or crisis resolution teams (CRTs)). Method: Quasi-experimental cohort study of women accessing acute psychiatric care up to 1 year postpartum in 42 healthcare organisations across England and Wales. Primary outcome was readmission within 12 months post-discharge. Propensity scores were used to account for systematic differences between MBU and non-MBU participants. Secondary outcomes included assessment of cost-effectiveness, experience of services, unmet needs, perceived bonding, observed mother–infant interaction quality and safeguarding outcome. Results: Of 279 women, 108 (39%) received MBU care, 62 (22%) generic ward care and 109 (39%) CRT care only. The MBU group ( n = 105) had similar readmission rates to the non-MBU group ( n = 158) (aOR = 0.95, 95% CI 0.86–1.04, P = 0.29; an absolute difference of −5%, 95% CI −14 to 4%). Service satisfaction was significantly higher among women accessing MBUs compared with non-MBUs; no significant differences were observed for any other secondary outcomes. Conclusions: We found no significant differences in rates of readmission, but MBU advantage might have been masked by residual confounders; readmission will also depend on quality of care after discharge and type of illness. Future studies should attempt to identify the effective ingredients of specialist perinatal in-patient and community care to improve outcomes.